Can people diagnosed as chronically mentally ill speak? - Michael May (Social Work and Society, 2023)
In this article, interaction forms of people who have experienced crises and users of mental health services are examined against the background of Gramsci's and Spivak´s concept of subalternity. To this end, first Foucault´s History of Madness is analysed in terms of hegemony theory. His concept of alienation is compared with that of Laing and related to Honneth´s theory of reification in order to explain, against this background and Lorenzer´s theory of interaction forms, how Foucault´s concept of disalienation is incorporated in modified form in the practice research network VISION-RA. Findings from this network on reifying interaction forms in the field of (community) psychiatry as well as on attempts of users of mental health services to resist these are presented. Following Spivak, the latter are interpreted as subaltern rebellion.